Vitamin D3 differentially regulates parathyroid hormone/parathyroid hormone-related peptide receptor expression in bone and cartilage - Amizuka, Norio (American Society for Clinical Investigation, 1999)
Transcription of the mouse parathyroid hormone (PTH)/PTH-related peptide (PTHrP) receptor (PTHR) gene is controlled by promoters P1 and P2. We performed transcript-specific in situ hybridization and found that P2 is the predominant promoter controlling PTHR gene expression in bone and cartilage. Treatment with 1α,25-dihydroxyvitamin D3 (D3) in vivo specifically downregulated P2-specific transcripts in osteoblasts, but not in chondrocytes, under conditions where it enhanced bone resorption. Treatment of the osteoblastic cell line MC3T3-E1 with D3 in vitro reduced expression of both P2-specific transcripts and PTHR protein. This effect was not blocked by cycloheximide, indicating that D3 inhibits PTHR expression by downregulating transcription of the P2 promoter. A similar inhibitory effect of D3 was not observed in the chondrocytic cell line CFK2. Gene-transfer experiments showed that P2, but not P1, is active in both MC3T3-E1 and CFK2 cells, and that D3 specifically inhibited P2 promoter activity in MC3T3-E1, but not in CFK2 cells. Inhibition of P2 activity by D3 required promoter sequences lying more that 1.6 kb upstream of the P2 transcription start site. Thus, the P2 promoter controls PTHR gene expression in both osteoblasts and chondrocytes. D3 downregulates PTHR gene transcription in a cell-specific manner by inhibiting P2 promoter activity in osteoblasts, but not in chondrocytes.